System of national standards for measuring and evaluating sound insulation. Issue 1 (January 2021) - Tsukernikov, Ilya; Shubin, I L; Nevenchannaya, T O
Abstract: The features of international standards being introduced in the Russian Federation in the field of measurement and rating of sound insulation are considered. It has been noted that over the past eight years, on the basis of international standards, a system of fundamental national standards of Russia has been created to measure and evaluate sound insulation in buildings and elements of buildings and structures. The system includes five standards that establish technical methods for laboratory measurements of airborne and impact sound insulation, a standard that establishes approximate methods for field measurements of airborne and impact sound insulation, two standards for a single-number assessment of airborne and impact sound insulation, a standard that sets the rules for determining and application of the uncertainties of sound insulation measurement. In 2018, 2019, on the basis of international standards, drafts of two national standards were prepared on the methods of field measurements of sound insulation of building facades and their elements and sound insulation of airborne sound between two rooms in a building.